Cognitive Mechanisms in Chronic Tinnitus: Psychological Markers of a Failure to Switch Attention - Trevis, Krysta J.; McLachlan, Neil M.; Wilson, Sarah J. (Frontiers in Psychology, 2016)
The cognitive mechanisms underpinning chronic tinnitus (phantom auditory perceptions) are underexplored but may reflect a failure to switch attention away from a tinnitus sound. Here, we investigated a range of components that influence the ability to switch attention, including cognitive control, inhibition, working memory and mood, on the presence and severity of chronic tinnitus. Our participants with tinnitus showed significant impairments in cognitive control and inhibition as well as lower levels of emotional wellbeing, compared to healthy-hearing participants. Moreover, the subjective cognitive complaints of tinnitus participants correlated with their emotional wellbeing whereas complaints in healthy participants correlated with objective cognitive functioning. Combined, cognitive control and depressive symptoms correctly classified 67% of participants. These results demonstrate the core role of cognition in chronic tinnitus. They also provide the foundations for a neurocognitive account of the maintenance of tinnitus, involving impaired interactions between the neurocognitive networks underpinning attention-switching and mood.